IMPLEMENTATION OF ONLINE CATALOGS: DATABASE MANAGEMENT SYSTEMS VS. BIBLIOGRAPHIC RETRIEVAL SYSTEMS/LA MISE EN OEUVRE DES CATALOGUES ORDINOLOINGUES: SYSTEMES DE GESTION DE BASES DE DONNES VS SYSTEMES DE REPERAGE BIBLIOGRAPHIQUE - Tague, Jean; Davies, Ronald; Toombs, Anne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF